The Impact of Earthquake and Liquefaction on The Socio-Economic Aspects of Farmers in Sigi District - Yanti, Sri; Darman, Saiful; Rauf, Rustam Abd.; Antara, Made; Hadayani, Hadayani (Postgraduate, University of Mataram, 2024)
The study aims to find out the impact of the earthquake and on the social and economic aspects and to know and analyzes the income after the earthquake and the cap. Like farmers in the Village of Jono Oge, Sidera and Sidondo 1 Sigi District Central Sulawesi Province. The Impact of a very all aspects except the social aspect except the social aspect The economy the loca community.This of research is descrivtive and quantitative. Research Descrivtive is resecearch that expalains the impact of social economic aspect, post-earth, liquefaction, and quantitative research is research that analyzes the data of observation results questionnaires and direct interview and documentation of tecniques using sampling proposive methods, with the number of respondent 148 people. The result of the study showed that the impact of earthquake dan developed on the Sociol economi aspect, namely: 1) The change in farmers activities due to the loss of propertyof shalter, thus encouraging some farmers to switch professions to meet their daily needs; 2) The amount of revenue of farmers before the earthquake in the Village of Jono Oge, Sidera and Sidondo 1, Sigi district City, with an average land area of 0.74 ha with an average revenue of IDR IDR 11.523.648,65 with an average total cost of IDR 4.474.400,34. So that the average income of IDR 7.049.248,31 For one time growing season; 3) The amount of revenue of farmers after the earthquake in the Village of Jono Oge, Sidera and Sidondo 1, Sigi district City, with an average land area of 0.68 ha with an average revenue of IDR IDR 11.796.875,00 with an average total cost of IDR 7.548.819,71 So that the average income of IDR 4.248.055,29 For one time growing season.